Strategies for Strengthening Character Education in Islamic Boarding Schools Through Extracurricular Activities - Huda, Nadya; Widodo, Bambang Sigit; Karwanto; Aseri, Muhsin; Wahyudin (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2024)
This study examines the role of extracurricular activities at Al Falah Islamic Boarding School in strengthening student character and the strategies implemented to achieve this goal. Employing qualitative methods such as interviews with key stakeholders and direct observations, the research highlights the significant impact of activities like scouting, Pagar Nusa martial arts, Palang Merah Remaja, rebana, and calligraphy in fostering values such as discipline, leadership, and empathy among students. Key strategies include embedding character values into the extracurricular curriculum, training program managers, diversifying activities to enhance student participation, and garnering support from families and communities. The findings reveal that structured and purposeful extracurricular programs effectively contribute to students’ character development. Leadership activities, humanitarian involvement, and cultural preservation impact essential values. Despite its contributions, the study acknowledges limitations, including small sample size, focus on a single institution, and lack of analysis across different age groups, student levels, or gender. The reliance on qualitative methods also suggests the need for further research involving broader and more varied samples, exploration of diverse educational settings, and a mixed-methods approach. These findings underscore the potential of extracurricular activities as a strategic avenue for character education in Islamic boarding schools.